Volatile organic compound analysis of accelerant detection canine distractor odours. (October 2019) - Leung, Douglas; Forbes, Shari; Maynard, Philip
Highlights: We demonstrate a specific analysis for odors in burnt samples using a GC/MS/MS method. The pyrolysis products were shown to contain target compounds of gasoline. High concentrations and a wide variety of individual target components were produced. False-positive responses by ILR canines may be due to pyrolysis of household items. These pyrolysis products are produced under realistic fire conditions. Abstract: Ignitable liquid detection dogs have been observed to falsely-respond to the pyrolysis products of common burned household items such as carpets and garden hoses, where ignitable liquids were not present. These responses from the canines are described as coming from distractor odours and decrease the reliability of detector dogs. The purpose of this research was to study the volatile organic compounds (VOCs) present in the odour profile of pyrolysed carpet and garden hose substrates, and determine whether a chemical similarity exists between these pyrolysis headspace profiles and target ignitable liquids, which may explain the false-positive behaviour of these detector dogs. Garden hose and carpet samples obtained from domestic settings were heated at a constant temperature for a specified time to produce pyrolysis products. A solid-phase microextraction (SPME) method was developed to extract the VOCs from burned substrates. The odours of the burned substrates were analysed by gas chromatography-mass spectrometry (GC/MS) and gas chromatography-tandem mass spectrometry (GC/MS/MS). A GC–MS/MS method was developed targeting the characteristic aromatic compounds in gasoline. Each pyrolysed substrate produced a complex and unresolved odour profile when analysed by GC- MS. GC–MS analysis failed to find any similarities between the odours of the burned substrates and ignitable liquids. GC–MS/MS analysis of pyrolysed garden hose and carpet substrate odours resolved and identified a wide range of aromatic target compounds – and these were present in high abundances in the hose samples. This indicates that there are significant chemical similarities between vapours of ignitable liquids and their distractor odours, which will have implications for the training of ignitable liquid detector dogs.